(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
The feminisation of education and particularly of elementary education has been a well-known fact for decades. However, when this issue is problematized, researchers tend to resort to common essentialist beliefis about the role of the sexes, instead of the interdisciplinary framing of the question. We have insufficient data on how the presence of male elementary teachers change the school climate and the teaching process itself; as well as the students’ gender socialisation, whether male elementary teachers influence their students’ gender identification in a radically different way from that of the female teachers, and if so how? Our research aims to find out what beliefs are present among the students and their parents about the male teachers. We also intend to explore how the male and female teachers themselves reflect on the interplay of their gender and professional identities.